A novel hybrid nonlinear control of four switch buck-boost converter feeding constant power load in fuel cell-based DC microgrid - Hafiz Mian Muhammad Adil; Hassan Abbas Khan (Results in Engineering)
Fuel cell-based DC microgrids (FC-DCMGs) offer clean, sustainable energy but face stability issues due to constant power loads (CPLs) and load-dependent fuel cell voltage. The four-switch buck-boost (4SBB) converter, with its non-inverting behavior and wide operating range, is ideal for interfacing fuel cells in DCMGs. However, robust control is crucial for seamless integration. This paper proposes a novel hybrid nonlinear controller for the CPL-fed 4SBB converter in FC-DCMGs to improve dynamic performance and robustness under load variations. The controller merges the robustness of supertwisting switching with the fast convergence of enhanced integral-based synergetic control. Control design is based on an average state-space model, incorporating a third-order polynomial model to estimate load-dependent fuel cell voltage. Controller parameters are optimized using the slime mould algorithm, minimizing the integral time absolute error (ITAE) to address both transient and steady-state behavior. Extensive simulations validate the performance of the proposed controller under varying resistive loads, changing CPL demands, and input voltage fluctuations. Compared with conventional sliding mode control (SMC) and Lyapunov function-based control (LFC), the proposed controller exhibits superior performance: a fast settling time of 1.8 ms (SMC: 5.7 ms, LFC: 25 ms), minimal overshoot of ≤4.16% (SMC: ≤6.87%, LFC: ≤5.20%), undershoot of ≤2.91% (SMC: ≤5%, LFC: ≤3.75%), retracing time of ≤2.5 ms (SMC: ≤5.5 ms, LFC: ≤20 ms), zero steady-state error, and no chattering. Furthermore, the real-time viability of the proposed controller is confirmed through controller hardware-in-the-loop (C-HIL) tests using the Texas Instruments TMS320F28379D Delfino Launchpad.